New Measure and Calculation Method for Gear Pair Normal Backlash - Song Shusen; Yang Lianbo; Xie Songsong; Yang Xiao; Wang Xin; Tang Haichuan (Jixie chuandong)
Calculated the gear pair normal backlash constant c according to definition and calculation method of gear pair normal backlash from GB/Z 18620.2—2008 at a given work center distance. One gear of the gear pair is fixed， the max rotation angle θ of the another rotatable gear is measured by using max rotation angle measure equipment. Gear pair normal backlash is acquired by product of gear pair normal backlash constant c and max rotation angle θ. Taking the measurement and calculation of the normal backlash of the gear pair of a balanced shaft assembly for an engine as an example， the equipment can be used to measure the normal backlash of gear pairs in the closed space is explained， the realization method for measure and calculation of the gear pair normal backlash introduced. The error source is explained and the error result is calculated. Compared with feeler gauge direct measure， the measured accuracy based on this method is verified. The normal backlash of the same mesh gear repeatedly is measured， the result consistency based on this method is verified.